Effects of rainbow trout (Oncorhynchus mykiss) cage culture on Western Cape irrigation reservoirs. - Maleri, Monika (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.